The Role of Philosophical Inquiry in Helping Students Engage in Learning - Leng, Lu (Frontiers in Psychology, 2020)
Studies have characterized high school students as bored, alienated, and disconnected with their class and the learning process. In order to address this problem to improve student learning engagement, this study explores the impact of philosophical inquiry on the development of adolescents’ academic engagement, and adds to the scholarly research on Philosophy for Children (P4C). In determining an appropriate and holistic approach to investigating students’ learning engagement and motivation from the perspective of psychology, this study involves multiple forms of data collection, specifically including surveys, student work, focus group interviews, classroom discussions, and reflective notes. Applying a qualitative method, this multiple case study developed a deeper understanding of the classroom contexts, conditions, discourses, tools and practices that promote positive adolescent learning experiences. The study developed a conceptual framework of student academic engagement in a philosophical inquiry class and summarized reasons why the participants engaged in learning. First, students believed that maintaining a safe and positive classroom environment is a fundamental condition for learning. Second, they reported that asking questions, sharing ideas, listening attentively, thinking deeply, and making connections are the manifestations of an engaging classroom. Third, students reported that they transcended their learning experiences by living a new philosophy that was acquired in the process of the community of inquiry. The study found that philosophical inquiry enhanced social inclusion and active participation of the participant in the learning process.